Chương 3: PHƯƠNG TRÌNH, HỆ PHƯƠNG TRÌNH

PH

\(\dfrac{x-1}{x+2}-\dfrac{x-2}{x+3}=\dfrac{x-4}{x+5}-\dfrac{x-5}{x+6}\)

RT
6 tháng 11 2018 lúc 22:59

ĐK \(x\ne-2;-3;-5;-6\)

\(\Leftrightarrow\dfrac{x-1}{x+2}-1-\left(\dfrac{x-2}{x+3}-1\right)=\dfrac{x-4}{x+5}-1-\left(\dfrac{x-5}{x+6}-1\right)\)

\(\Leftrightarrow\dfrac{x-1-x-2}{x+2}-\dfrac{x-2-x-3}{x+3}=\dfrac{x-4-x-5}{x+5}-\dfrac{x-5-x-6}{x+6}\)

\(\Leftrightarrow\dfrac{-3}{x+2}-\dfrac{-5}{x+3}=\dfrac{-9}{x+5}-\dfrac{-11}{x+6}\)

\(\Leftrightarrow\dfrac{3}{x+2}-\dfrac{5}{x+3}=\dfrac{9}{x+5}-\dfrac{11}{x+6}\)

\(\Leftrightarrow\dfrac{3}{x+2}+\dfrac{11}{x+6}=\dfrac{9}{x+5}+\dfrac{5}{x+3}\)

\(\Leftrightarrow\dfrac{3\left(x+6\right)+11\left(x+2\right)}{\left(x+2\right)\left(x+6\right)}=\dfrac{9\left(x+3\right)+5\left(x+5\right)}{\left(x+3\right)\left(x+5\right)}\)

\(\Leftrightarrow\dfrac{14x+40}{\left(x+2\right)\left(x+6\right)}=\dfrac{14x+52}{\left(x+3\right)\left(x+5\right)}\)

\(\Leftrightarrow\left(x+2\right)\left(x+6\right)\left(14x+52\right)=\left(x+3\right)\left(x+5\right)\left(14x+40\right)\)

\(\Leftrightarrow\left(x^2+8x+12\right)\left(14x+52\right)=\left(x^2+8x+15\right)\left(14x+40\right)\)

\(\Leftrightarrow14x\left(x^2+8x+12\right)+52\left(x^2+8x+12\right)=14x\left(x^2+8x+15\right)+40\left(x^2+8x+15\right)\)

\(\Leftrightarrow14x\left(x^2+8x\right)+12.14x+52\left(x^2+8x\right)+52.12=14x\left(x^2+8x\right)+15.14x+40\left(x^2+8x\right)+15.40\)

\(\Leftrightarrow12\left(x^2+8x\right)-42x+24=0\)

\(\Leftrightarrow12x^2+54x+24=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x=-4\end{matrix}\right.\)

Bình luận (0)

Các câu hỏi tương tự
NC
Xem chi tiết
NS
Xem chi tiết
LN
Xem chi tiết
TY
Xem chi tiết
PH
Xem chi tiết
TL
Xem chi tiết
NH
Xem chi tiết
TN
Xem chi tiết
KR
Xem chi tiết